Karyological analysis of an interspecific hybrid between the dioecious Silene latifolia and the hermaphroditic Silene viscosa - Markova, Michaela; Lengerova, Martina; Zluvova, Jitka; Janousek, Bohuslav; Vyskot, Boris (Genome, 2006)
The genus Silene is a good model for studying evolution of the sex chromosomes, since it includes species that are hermaphroditic and dioecious, while maintain a basic chromosome number of 2n = 24. For some combinations of Silene species it is possible to construct interspecific hybrids. Here, we present a detailed karyological analysis of a hybrid between the dioecious Silene latifolia as the maternal plant and a related species, hermaphroditic Silene viscosa, used as a pollen partner. Using genomic probes (the genomic in situ hybridization (GISH) technique), we were able to clearly discriminate parental genomes and to show that they are largely separated in distinct nuclear domains. Molecular GISH and fluorescence in situ hybridization (FISH) markers document that the hybrid genome of somatic cells was strictly additive and stable, and that it had 12 chromosomes originating from each parent, including the only X chromosome of S. latifolia. Meiotic analysis revealed that, although related, respective parental chromosomes did not pair or paired only partially, which resulted in frequent chromosome abnormalities such as bridges and irregular non-disjunctions. GISH and FISH markers clearly document that the larger genome of S. latifolia and its largest chromosome component, the X chromosome, were mostly employed in chromosome lagging and misdivision.
Keywords: chiméra; poruchy sexuálního vývoje; Genome, Plant; genom rostlinný; karyotypizace; Silene; Crosses, Genetic; hybridizace in situ fluorescenční; fylogeneze; Phylogeny; Karyotyping; Meiosis; chromozom X; chromozomy rostlin; Chromosomes, Plant; X Chromosome; meióza; segregace chromozomů; křížení genetické; Chimera; In Situ Hybridization, Fluorescence; Chromosome Segregation; Disorders of Sex Development